Doing business in Spain - Kasianova, Anastasiia; Bolotov, Ilya; Cook, Gina, 1970-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The goal of the thesis is to examine the business environment in Spain, to trace how the economy was changing from the times of autarky until the current time. In addition, to find out what were the causes of the crisis and what Spain did in order to recover from it, to look at the legal framework of doing business in Spain
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses